Bioethics for clinicians: 23. Disclosure of medical error - Hébert, Philip C. (2001)
ADVERSE EVENTS AND MEDICAL ERRORS ARE NOT UNCOMMON. In this article we review the literature on such events and discuss the ethical, legal and practical aspects of whether and how they should be disclosed to patients. Ethics, professional policy and the law, as well as the relevant empirical literature, suggest that timely and candid disclosure should be standard practice. Candour about error may lessen, rather than increase, the medicolegal liability of the health care professionals and may help to alleviate the patient's concerns. Guidelines for disclosure to patients, and their families if necessary, are proposed.